(untitled) (Journal of Oriental Studies, 2016)
In the article the using of phrase logical locutions as one of the peculiarities of political discourse texts has been shown. Phrase logical locutions make a function of emotional influence on the recipient. From translational point of view phrase logical locutions feature big difficulties, because of their specific national coloring.